Strengthening the emergency care system at a primary health care level using a framework for policy analysis - Botes, Meghan Lavina (My University, 2021)
Health care systems, globally, have moved towards a focus on prevention and promotion; however strengthening emergency care at a primary health care level is vital for reducing overall mortality and disability (World Health Assembly, 2015). Emergency care exists within the broader system of health care and in order to understand and improve the system of emergency care an investigation that extracts insights from the various cogs in the system is needed. The objectives of the study were to analyse the system of emergency care using Walt and Gilson’s policy analysis framework, formulate evaluative conclusions, and to develop recommendations for strengthening the system of emergency care at a primary health care level. A qualitative formative evaluation approach was used. The study was conducted in the Gauteng District Health System at various level one health care facilities. The first phase of the study focused on collecting data using semi structured interviews and analysis of data using qualitative content analysis. Using maximum variation sampling, participants (n=22) included health care practitioners, and health care facility managers. A document analysis of policies and guidelines that inform the district heath system was undertaken in conjunction with key informant interviews. The second phase included the formulation of recommendations by way of deductive reasoning and inviting key informants to validate the recommendations using the Delphi technique. Ethical considerations were applied. Emergency care in the District Health Care system was described and evaluated based on findings from the three data sources identified in the framework for policy analysis. Triangulation of the data was achieved using the same framework for policy analysis and strengths and weaknesses in the system of emergency care were identified. Evaluative conclusions were formulated, and recommendations for strengthening emergency care in the District Health Care system were developed based on these. Fourteen consensus-based recommendation statements were presented as the outcome of the research study. The recommendations proposed cover various aspects in need of improvement in the emergency care system including education and training, the role and placement of various actors, the need for leadership in emergency care and the need for a national plan for emergency care. Emergency care needs to become a priority in the National Health System.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2021